Brain–immune–gut benefits with early life supplementation of milk fat globule membrane. Issue 7 (1st June 2022) - Mohamed, Hamid Jan Jan; Lee, Eric Kim Hor; Woo, Kent Chee Keen; Sarvananthan, Rajini; Lee, Yeong Yeh; Mohd Hussin, Zabidi Azhar
Abstract: The milk fat globule membrane (MFGM) has been recognized as a milk component for more than 60 years, but its exact benefits remain unknown. Research on human MFGM has revealed that the membrane holds a host of bioactive components with potential benefits for the brain–immune–gut (BiG) axis in early life. Gangliosides and sphingomyelin, components within the MFGM, have been included in infant formulas for many years. Recent advancements in dairy milk processing have allowed the successful separation of MFGM from bovine milk, enabling it to be used for supplementing infant formulas. Evidence indicates the potential benefits of MFGM in early life supplementation, including better cognitive development, reduction of infection risks, and modulation of the gut microbiome. However, larger and more robust randomized trials are needed, in addition to long‐term outcome data beyond the infancy period. Abstract : The milk fat globule membrane (MFGM) has been recognized as a milk component for more than 60 years, but its exact benefits remain unknown. Research on human MFGM has revealed that the membrane holds a host of bioactive components with potential benefits for the brain–immune–gut axis in early life. Evidence indicates the potential benefits of MFGM in early life supplementation, including better cognitive development, reduction of infection risks, and modulation of the gut microbiome.